The therapeutic effect of citrus aurantifolia swingle in idiopathic hypocitraturic calcium nephrolithiasis - Mochammad Sja’bani, Mohammad Ismadi, Siti Dawiesah Ismiati, Raja Pingkir Sidabutar, Djoko Rahardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Hypocitraturia is one of the main risks of stone appearance or renal stone recurrence that iseasily interfered. A sphere citrus fruit (Citrus aurantifolia Swingle) was reported to contain the highestcitrate compared to other citrus fruits.Aims: We aimed to determine the effect of Citrus aurantifolia Swingle on the management of hypocitraturia,compared with potassium citrate.Materials and Methods: Seventy two patients with idiopathic calcium renal stone with hypocitraturia wererandomly divided into two groups, therapy and placebo groups. The first group was given potassium citratetreatment (2x20 mEq/day), while the second one was given 2x1.5-g pure lactose. After 6 months,patients without stomachache complaints were given 40ml citrus juice diluted in 2 glasses of water, takenimmediately after dinner for 10 days. Observation was done on risk factors in urine collected for 8, 16 and24-hours, including volume, pH, potassium, magnesium, oxalate, citrate, calcium, sodium, phosphate,sulphate, uric acid, ureum and creatinine. The setting of this study was 1 hospital in Yogyakarta and 2hospitals in Jakarta.Results: The increase of urine volume, pH, level and total citrate value, level and total potassium, and thedecrease of calcium ratio to citrate urine. The changes of those metabolite levels could lessen the chanceof colic and hematuria complaints, as seen after 6 months administation of potassium citrate. Similarresults were obtained from the administration of citrus juice, except for calcium level, which was notdecreased.Conclusion: The administration of potassium citrate 2x20mEq/day in 6 months improved patient’s complaintsand occurrence of renal colic, while consumption of Citrus aurantifolia Swingle in idiopathic calcium renalstone with hypocitraturia was concluded to increase the urine volume, pH level and total citrate value,level and total potassium, and the decrease of calcium ratio to urine citrate.Key word: renal stone- hypocitraturia- Citrus aurantifolia Swingle